Nomenclatura de las rocas pelíticas (2017)
This paper seeks to unify the terminology and nomenclature of the pelitic rocks in lithostratigraphic descriptions of the subsoil. It is aimed at students of Petroleum Engineering and related, as a reference material, and all those professionals and technicians related to hydrocarbon deposits who wish to expand their knowledge on the subject. The goal is not to create a new taxonomic classification of rock or sediment names. On the contrary, what is recommended is that all the compositional or textural subtypes can be considered as traditionally done, with systems of two, three or four components, that is, with the triangles and traditional statistical tetrahedra.